PERBANDINGAN REGULASI PENANGANAN KEJAHATAN TERORISME DI INDONESIA DAN MALAYSIA - Andre Setiawan, Adji Rahmat; Dwi Putranto , Rachmat (Journal Evidence Of Law, 2023)
Indonesia is one of the countries with a considerable impact of terrorism, Indonesia should pay great attention to the development of radical currents and terrorist organizations. Terrorism is a major threat to the resilience and security of all Indonesian people. Even terrorism is becoming a common enemy around the world. Indonesia is one of the countries that faces a high level of terrorism cases. The Global Terrorism Index is published by the Institute for Economics and Peace. Indonesia is in 38th position out of 143 countries worldwide in terms of terrorism cases, Indonesia has issued regulations related to terrorism designed based on the Bali I bombing on October 12, 2002. Comparison with Malaysia shows that the country was ranked 61st out of 143 countries in the Global Terrorism Index 2016 with a value of 2,691. The author is interested in analyzing the differences in regulation in the handling of crime in the two countries, with the title comparison of regulation on the handling of terrorism crimes in Indonesia and Malaysia. This study uses normative legal research methods that are prescriptive analysis by reviewing legislation.